Institutional governance and financial management for rural welfare: The dual moderating role of Tri Hita Karana in Bali's independent villages - Jayanthi, Ni Kadek Eka; Marhaeni, Anak Agung Istri Ngurah; Dewi, Made Heny Urmila; Yasa, I Nyoman Mahaendra (Edelweiss Applied Science and Technology, 2025)
This study examines how village governance and financial management influence the welfare of independent village communities in Bangli, Bali, with Tri Hita Karana as a moderating variable. Using a quantitative method and SEM-PLS analysis, data were collected from 68 villages through questionnaires distributed to village leaders and officials. Results show that both governance and financial management significantly improve community welfare. Although Tri Hita Karana does not directly affect welfare, it plays a dual moderating role: weakening the impact of governance but strengthening financial management's effect on welfare, highlighting the complex interaction between cultural values and formal institutions. Furthermore, Importance-Performance Map Analysis (IPMA) identifies education, training, and financial accountability as key areas to improve welfare outcomes. The study emphasizes the need for integrating effective governance practices with local cultural wisdom to support sustainable rural development and offers policy recommendations for culturally responsive village planning.